Age-related macular degeneration: a review of current therapies and new treatments - Kniggendorf,Vinicius (2020)
ABSTRACT Age-related macular degeneration is the leading cause of vision loss in elderly individuals, as well as a medical and socio-economic challenge. The treatment of dry age-related macular degeneration is based on vitamin supplementation. New treatment studies are focused on preventing the progression of degeneration and repopulating the atrophic macula. Recently, research on the treatment of neovascular age-related macular degeneration experienced a breakthrough with the advent of anti-vascular endothelial growth factor inhibitors. Nevertheless, despite the fact that ranibizumab, aflibercept, and bevacizumab are effective in reducing severe visual impairment, patients usually lose some vision over time. Therefore, the search for new therapies and diagnostic methods is fundamentally important. Current studies are focused on new anti-vascular endothelial growth factor drugs, nucleoside reverse transcriptase inhibitors, antibody against sphingosine-1-phosphate, anti-platelet-derived growth factor, gene therapy, and RNA interference. The results of ongoing clinical studies may improve the therapy of age-related macular degeneration.